Non-pathogenic trade-offs of wastewater irrigation - Qadir, Manzoor; Scott, Christopher A. (2010)
The volume and extent of urban wastewater generated by domestic, industrial and commercial water use has increased with population, urbanization, industrialization, improved living conditions and economic development. Most developing-country governments do not have sufficient resources to treat wastewater. Therefore, despite official restrictions and potential health implications, farmers in many developing countries use wastewater in diluted, untreated or partly treated forms with a large range of associated benefits. Aside from microbiological hazards, the practice can pose a variety of other potential risks: excessive and often imbalanced addition of nutrients to the soil; build-up of salts in the soils (depending on the source water, especially sodium salts); increased concentrations of metals and metalloids (particularly where industries are present) reaching phytotoxic levels over the long term; and accumulation of emerging contaminants, like residual pharmaceuticals. As these possible trade-offs of wastewater use vary significantly between sites and regions, it is necessary to carefully monitor wastewater quality, its sources and use for location-specific risk assessment and risk reduction.